VCP Machinery Mediates Autophagic Degradation of Empty Argonaute - Hotaka Kobayashi; Keisuke Shoji; Kaori Kiyokawa; Lumi Negishi; Yukihide Tomari (Cell Reports, 2019)
Summary: The Argonaute subfamily of proteins (AGO) loads microRNAs (miRNAs) to form the effector complex that mediates target gene silencing. Empty AGO, but not miRNA-loaded AGO, is selectively degraded across species. We have reported that the degradation of empty AGO is part of a quality control pathway that eliminates dysfunctional AGO. However, how empty AGO is degraded remains unclear. Here we show that the empty state of Drosophila Ago1 is degraded by autophagy. Comprehensive LC-MS/MS analyses, together with manipulation of the Ago1 ubiquitination level, revealed that VCP, which mediates selective autophagy, recognizes empty Ago1 via the Ufd1-Npl4 heterodimer. Depletion of VCP-Ufd1-Npl4 machinery impairs degradation of empty Ago1 and miRNA-mediated target gene silencing. Our findings reveal a direct link between empty AGO degradation and selective autophagy that ensures efficient miRNA function. : Empty Argonaute proteins that are not loaded with microRNAs are selectively degraded across species. Kobayashi et al. report that VCP, a mediator of selective autophagy, recognizes empty Argonaute via the Ufd1-Npl4 heterodimer to direct its degradation and that VCP-Ufd1-Npl4 machinery is required for efficient gene silencing by microRNAs. Keywords: Argonaute, microRNA, RNA silencing, ubiquitin, VCP, autophagy